Survey of General Pediatricians’ Referral Patterns for Undescended Testis - Hammad Aslam, Atika Urooj, Sidra Ashraf, Javeria Zafar, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Undescended testis is one of the most common congenital anomalies in male infants and requires timely referral for surgical correction to reduce the risk of infertility, malignancy, and other long-term complications. Objective: To assess the referral patterns of general pediatricians for undescended testis and evaluate their knowledge, clinical practices, and adherence to guideline-recommended referral timelines. Methods: This was a descriptive, cross-sectional survey conducted at Jinnah hospital Lahore from June 2022 to June 2023 including 75 general pediatricians involved in routine pediatric care. The study was designed to assess referral patterns, clinical decision-making, and adherence to guideline-recommended practices for the management of undescended testis. Results: 42.7% of the sample had 35-45 years of age, and 37.3% had over 10 years of clinical experience. The majority of pediatricians had the correct knowledge of undescended testis (72.0%) and only 52.0% had the reliability of differentiating between the two (undescended and retractile testis). Knowledge on fertility-related complications was found in 76.0 and on malignancy risk was found in 57.3%. Though the majority felt that referral was appropriate at or before 12 months, using 57.4% of the people who thought so, only a quarter of the people practiced immediate referral. Remarking at six months was reported, by 37.3 and 14.7 stayed at two years delay at referral. Pediatricians applied pre-referral imaging in 54.7% of cases and it was linked with delayed referral. The highest referral rates were by the pediatricians who had less than five years’ experience (66.7%) and the lowest by those who had more than ten years of experience (32.1%). Conclusion: There is a high level of referral practices of undescended testis among general pediatricians which are characterized by delays beyond the recommended schedules. The major causes of delayed referral were diagnostic uncertainty, incomplete awareness of guidelines, and the use of pre-referral imaging. Keywords: Undescended testis; Cryptorchidism; Pediatric referral patterns; Orchidopexy; Pediatric surgery